3D inkjet printing of tablets exploiting bespoke complex geometries for controlled and tuneable drug release - Kyobula, Mary; Adedeji, Aremu; Alexander, Morgan R.; Saleh, Ehab; Wildman, Ricky D.; Ashcroft, Ian; Gellert, Paul R.; Roberts, Clive J. (Elsevier, 2017)
A hot melt 3D inkjet printing method with the potential to manufacture formulations in complex and adaptable geometries for the controlled loading and release of medicines is presented. This first use of a precisely controlled solvent free inkjet printing to produce drug loaded solid dosage forms is demonstrated using a naturally derived FDA approved material (beeswax) as the drug carrier and fenofibrate as the drug. Tablets with bespoke geometries (honeycomb architecture) were fabricated. The honeycomb architecture was modified by control of the honeycomb cell size, and hence surface area to enable control of drug release profiles without the need to alter the formulation. Analysis of the formed tablets showed the drug to be evenly distributed within the beeswax at the bulk scale with evidence of some localization at the micron scale. An analytical model utilizing a Fickian description of diffusion was developed to allow the prediction of drug release. A comparison of experimental and predicted drug release data revealed that in addition to surface area, other factors such as the cell diameter in the case of the honeycomb geometry and material wettability must be considered in practical dosage form design. This information when combined with the range of achievable geometries could allow the bespoke production of optimized personalised medicines for a variety of delivery vehicles in addition to tablets, such as medical devices for example.